2019
DOI: 10.1093/nar/gkz570
|View full text |Cite
|
Sign up to set email alerts
|

Binding of eIF3 in complex with eIF5 and eIF1 to the 40S ribosomal subunit is accompanied by dramatic structural changes

Abstract: eIF3 is a large multiprotein complex serving as an essential scaffold promoting binding of other eIFs to the 40S subunit, where it coordinates their actions during translation initiation. Perhaps due to a high degree of flexibility of multiple eIF3 subunits, a high-resolution structure of free eIF3 from any organism has never been solved. Employing genetics and biochemistry, we previously built a 2D interaction map of all five yeast eIF3 subunits. Here we further improved the previously reported in vitro recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 73 publications
(147 reference statements)
2
27
0
Order By: Relevance
“…A recent study using advanced mass spectrometry revealed that the yeast eIF3 complex in solution adopts a globular 3D structure, with the WD40 domains/β-propellers of eIF3b and eIF3i, the RRMs of eIF3b and eIF3g and the N-and C-terminal ends of eIF3a and eIF3c all exposed to the surface. Interestingly, the PCI domains of eIF3a and eIF3c do not interact with each other in the free eIF3 complex (Zeman et al, 2019). This stands in contrast to the interaction between the two PCI domains observed in the structures of eIF3 present in various conformational states of the PIC, wherein the eIF3 complex seems to have undergone a large conformational change on binding to the 40S subunit (Hashem et al, 2013) (Aylett et al, 2015) 4 (Llácer et al, 2015) (Llácer et al, 2018) (des Georges et al, 2015) (Eliseev et al, 2018).…”
Section: Introductionmentioning
confidence: 90%
“…A recent study using advanced mass spectrometry revealed that the yeast eIF3 complex in solution adopts a globular 3D structure, with the WD40 domains/β-propellers of eIF3b and eIF3i, the RRMs of eIF3b and eIF3g and the N-and C-terminal ends of eIF3a and eIF3c all exposed to the surface. Interestingly, the PCI domains of eIF3a and eIF3c do not interact with each other in the free eIF3 complex (Zeman et al, 2019). This stands in contrast to the interaction between the two PCI domains observed in the structures of eIF3 present in various conformational states of the PIC, wherein the eIF3 complex seems to have undergone a large conformational change on binding to the 40S subunit (Hashem et al, 2013) (Aylett et al, 2015) 4 (Llácer et al, 2015) (Llácer et al, 2018) (des Georges et al, 2015) (Eliseev et al, 2018).…”
Section: Introductionmentioning
confidence: 90%
“…With yeast eIF3a as the FOI, we observed an ~50 fold increase in the 80S FP coverage along the eIF3b (PRT1) mRNA for eIF3a::80S FPs versus unselected 80S FPs starting near nucleotide 580 and persisting until the end of the CDS ( Figure 7B). The onset of this increase is ~30 codons downstream of the CDS region that encodes the eIF3b RNA recognition motif (RRM; nucleotides 237 -477), which is one of the two main interacting domains for eIF3a within the eIF3 complex ( Figure S1A) (Valášek et al, 2002;Zeman et al, 2019). As the ribosome exit tunnel accommodates ~24 amino acids in extended conformation and ~38 amino acids in α-helical conformation (Bhushan et al, 2010), the nascent RRM should have just emerged from the ribosome when an increase in FP coverage is seen.…”
Section: Sel-tcp-seq Reveals Another Layer Of Regulation Of Gcn4/atf4mentioning
confidence: 99%
“…These schematics illustrate similarities and differences between budding yeast and mammalian eIF3. One of the main structural domains shared by several eIF3 subunits -the PCI (for Proteasome, COP9, Initiation factor 3) domain -is shown in bold in both panels; adopted from (Zeman et al, 2019). (C, D) Schematic representation of the arrangement of eIF3 subunits in the two available conformations that are deduced from the available Cryo-EM analysis (adapted from ).…”
Section: Supplemental Figure Legendsmentioning
confidence: 99%
See 1 more Smart Citation
“…In yeast, the PCI-MPN core consists of the two subunits eIF3a (Rpg1/Tif32) and eIF3c (Nip1), whereas in mammals, it is formed by an octamer of eIFs 3a, 3c, 3e, 3f, 3h, 3i, 3k and 3l (Valasek et al, 2017). The peripheral subunits consist of the socalled yeast-like core (YLC) module, containing eIF3b (Prt1), eIF3g (Tif35), and eIF3i (Tif34), as well as the C-terminus of eIF3a, the N-terminal domain of eIF3c that interacts with eIF1 and eIF5 (Valasek et al, 2003;Valasek et al, 2004;Yamamoto et al, 2005;Zeman et al, 2019), and in mammals eIF3d. In addition, eIF3j is associated with eIF3 but does not belong to its core, and plays a special role (Block et al, 1998;Valasek et al, 1999).…”
Section: Introductionmentioning
confidence: 99%